Art & Language International : Conceptual Art between Art Worlds - Bailey, Robert, 1983- (Book collections on Project MUSE., 2016)
Robert Bailey reconstructs the history of conceptual art collective Art & Language to show how its international collaborations with dozens of artists and critics between 1969 and 1977 laid the foundation for global contemporary art, all while highlighting how conceptual art exceeds the visual to impact the philosophical and political.